Implementation of Verified Containers Carried on Ships (Gross Mass and Container Verification) – VGM at Belawan Container Terminal - Jumriani, Jumriani; Rachman, Subehana; Rahma, Annisa; Asnur, Asnur (Dinasti Publisher, 2024)
Abstract: Implementation of Verified Containers Carried on Ships (Verified Gross Mass of Container) – VGM at Belawan Container Terminal (Research Team Supriadi and Christy Pongkessu). In an effort to improve shipping safety and minimize the risk of damage or accidents at sea due to load imbalance and overloading on ships, in May 2014 the International Maritime Organization - The Maritime Safety Committee (IMOMSC) has decided to approve changes to The International Convention for the Safety of Life at Sea (SOLAS) 1974 Chapter VI Article 2 concerning the requirements for verifying the gross weight of containers (Verified Gross Mass of Container/ VGM). Verified Gross Mass (VGM) is validated container weight information using scales that have been certified and accounted for by a verifier. This study aims to determine the implementation and impact of the implementation of Verified Gross Mass (VGM) at Belawan Port. This research was conducted at Belawan Port located in Medan City, North Sumatra, Indonesia for 6 (six) months, namely from May to October 2023. The type of research used is qualitative research. Qualitative research methods are research methods based on the philosophy of postpositivism, data collection techniques with triangulation (combined), inductive/qualitative data analysis. Based on the results of the study, it was concluded that Belawan Port has implemented the Verified Gross Mass (VGM) procedure in accordance with SOLAS (Safety of Life at Sea) regulations. This process involves verifying the gross weight of containers before loading onto ships using appropriate weighing equipment. The main impact of implementing Verified Gross Mass (VGM) is increasing the safety of container ship navigation. By ensuring the correct gross weight of containers, ports can prevent ship accidents caused by gross weight inaccuracies. Keywords: Shipping Safety, Containers, Verified Gross Mass